SOME DETECTIONS REGARDING CULTURAL CODINGS IN 8TH GRADE ENGLISH EDUCATION MATERIAL IN TURKEY - Uğurlu, Mesut (International Scientific Journal Vision, 2023)
According to the realist approach, states act in line with their own interests. Therefore, in terms of economic, political, military and cultural terms, each state tries to strengthen its position. In order to be stronger in terms of culture, states are trying to transfer their cultures to other cultures. In this way, states want to create sympathy for their own culture. This will benefit them both in terms of tourism and qualified workforce. There are other positive effects of the fact that the culture of a country is sympathized by other citizens of the country. Therefore, each country wants to coding its culture to the cultures of other states. One of these cultural coding tools is foreign language education. Foreign language education in Turkey is mainly in English. English education is provided as a foreign language in primary and secondary education institutions. In our study, the English education material was selected as an example of the 8th grade students of primary education as a sample. The special cultural coding elements in this material were identified. However, general cultural coding elements were determined. This determination was analyzed comparatively with the general cultural coding methods on the Voice of America Learning English website.